The differences in ethnic and gender on communication styles among public university students in Klang Valley, Malaysia - Azmi, Syasya Firzana; Ma’rof, Aini Azeqa; Abdullah, Haslinda; Zarimohzzabeih, Zeinab (Human Resource Management Academic Research Society, 2023)
Understanding the differences in ethnic and gender communication styles in the Malaysian context is crucial for fostering inclusive and effective communication, promoting cultural sensitivity, and reducing potential biases or misunderstandings that may hinder successful interpersonal interactions. Therefore, the main purpose of this study is to determine the differences in communication styles between gender and ethnic group among public university students in Klang Valley, Malaysia. 380 students have participated in this study involving three Malaysian public universities by stratified sampling. A self-administered questionnaire was used in collecting the data and it was analyzed using the Statistical Package for Social Sciences (SPSS) by employing t-tests and correlations. The result shows that the Malay respondents perceive themselves as dramatic, open, and dominant meanwhile Chinese respondents perceive themselves as being attentive, animated, yet argumentative. Meanwhile, the differences in communication styles among gender show that female respondents perceive themselves as more dramatic, open, and dominant. Understanding the impact of gender and ethnic differences in communication styles within the Malaysian context promotes harmonious relationships, cultivates cultural empathy, and facilitates effective communication, leading to a more inclusive and cohesive society. This knowledge helps bridge cultural gaps, fosters mutual respect, and enables individuals to navigate diverse perspectives with sensitivity and understanding.